Prematuritas Gugatan Class Action: Analisis Konflik Norma antara Pasal 29 AB dan Pasal 78 Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup dalam Putusan MA No. 4441 K/Pdt/2024 - Sri Amelia Dewi; Syamhudian Noor; Ariani Yestati; Fransisco Fransisco (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the conflict between the application of Article 29 of the AB and Article 78 of the Environmental Protection and Management Law (UU PPLH) in determining the prematurity of a lawsuit for environmental torts in Supreme Court Decision No. 4441 K/Pdt/2024. This normative legal research employs statutory, conceptual and case-based approaches. The results of the study indicate that Article 78 of the Environmental Protection and Management Law is more appropriately applied because it allows for the parallel enforcement of administrative, civil and criminal law, thereby ensuring that ongoing criminal proceedings do not render a civil environmental lawsuit premature. Thus, a decision that bases the prematurity of a lawsuit on an unresolved criminal process potentially hinders the effectiveness of environmental protection and restoration.